How Pope Pius IX Stimulated 'Pillarization' in the Netherlands - Hans Knippenberg (Historical Life Course Studies)
In 1853 an important step in the development of the Roman Catholic Church in the Netherlands was set. On initiative of the Vatican and despite vehement resistance of the orthodox Protestant part of the population (known as the April-movement), the episcopal hierarchy in the church was restored. By choosing Utrecht in the heart of the protestant Netherlands and not Den Bosch in the Catholic South of the country as the seat of the new archbishop, the Vatican practised an offensive, national strategy. Unintendedly, the Papal choice for Utrecht contributed to the later on development of the non-territorial, personalistic solution for the Dutch multicultural society at that time: the verzuiling.